Transformation of Palembang Malay Language Politeness in Arab Village Sei Bayas: An Innovative Socio-Pragmatic Study - Sri Parwanti; Ris'an Rusli; Masyhur Masyhur (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyse the transformation of Palembang Malay politeness in the social interaction of the Arab Village Sei Bayas community, using an innovative socio-pragmatic approach. The main focus of this study is to identify politeness strategies as well as the community's ability to express directive speech acts politely and according to context. The phenomenon of shifting politeness values in Palembang Malay language practices is the main background of this research. The method used is qualitative, through observation and in-depth interviews with people in RT 02 and RT 26, with a total of 40 respondents and 4 representative speakers. Data analysis was conducted based on Searle's theory of directive speech acts, which includes forms of requests, questions, orders, prohibitions, giving permission, and advice. The results showed that directive speech acts in the form of requests dominated in 43 interaction situations. In addition, a significant influence of Javanese language on the forms of speech in the local Palembang Malay language was found. This finding confirms the process of politeness transformation influenced by cultural and language contact, as well as making an important contribution to the development of socio-pragmatic studies and understanding the linguistic dynamics of traditional communities in contemporary social contexts.